Neurocognitive functioning of children with mild to borderline intellectual disabilities and psychiatric disorders: profile characteristics and predictors of behavioural problems. - Santegoeds, E.; van der Schoot, E.; Roording‐Ragetlie, S.; Klip, H.; Rommelse, N. (Journal of Intellectual Disability Research)
Background: The aim of the current study was twofold: first, to uncover a neurocognitive profile of normative and relative strengths and weaknesses that characterises an extremely vulnerable group of children with mild to borderline intellectual disabilities (MBID) and co‐morbid psychiatric disorders, and second, to investigate the relevance of these neurocognitive functions explaining internalising and externalising symptoms. Method: We recruited 45 children (Mage = 9.5, SDage = 1.7; range 6–13 years) with MBID (Full‐Scale IQ 50–85) and at least one psychiatric disorder. Neurocognitive functioning was examined utilising the Wechsler Intelligence Scale for Children – Fifth Edition (WISC‐V) indices and the Cognitive Task Application (COTAPP), a comprehensive computerised self‐paced task designed in such a manner that 'g' (an overall tendency of children with MBID to execute tasks with a slower reaction time and a higher error rate) has been corrected for in the administration of the task (i.e. completely self‐paced) and in the operationalisation of outcome measures. Behavioural problems were measured using the CBCL and TRF. One‐sample t‐tests and binomial tests were carried out to compare performance with normative data. Regression analyses were used to examine the relationship between neurocognitive parameters and mental health. Results: Compared with normative data, very small to very large effect sizes were found, indicating clear heterogeneity amongst neurocognitive domains relevant for children with MBID. Two prominent neurocognitive weaknesses emerged: processing speed – characterised by slowness and unstableness combined with a high drift rate and delayed processing of the previous trial, particularly under higher cognitive demands – and working memory – in terms of a weaker central executive and 'slave' systems to temporarily store information. Both domains were not clearly predictive of internalising or externalising problems. Conclusion: Children with MBID and psychiatric disorders are hampered by a strongly diminished processing speed and working memory capacity, together resulting in an overall limited processing capacity that may underlie the general developmental delays on domains that depend on fast and parallel processing of information (i.e. language, reading, mathematics and more complex forms of social cognition). Neurocognitive vulnerabilities are neither necessary nor sufficient to explain internalising and externalising problems; rather, a mismatch between the support needs and adaptations these children need, arising from their diminished processing capacity, and the inadequacy of the environment to compensate for this vulnerability may be of relevance.